O dólar como moeda internacional e os limites da autonomia de política econômica dos Estados Unidos - Arienti, Patricia Fonseca Ferreira (Meridiano 47 - Journal of Global Studies, 2017)
The United States has relied heavily on reserve accumulation by foreign central banks to finance its current account deficit since 2000 on. However, the currency composition of reserves has changed gradually over the past decade and the share of U.S. dollar holdings has steadied. This fact may imply that the U.S. will need to start its adjustment process very soon.